Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Pelanggan pada Gerai Tiki 0259 di Kabupaten Bekasi - Rickyanto Ames; Usran Masahere (Global Leadership Organizational Research in Management, 2025)
This study aims to analyze the influence of service quality and facilities on customer satisfaction at Tiki 0259 Outlet in Bekasi Regency. In the era of increasingly competitive logistics service industry, customer satisfaction is the key to the sustainability and growth of the company. Tiki 0259, as one of the providers of goods delivery services, must be able to maintain service quality and provide adequate facilities to maintain customer loyalty. The research method used is quantitative with a survey approach. Data were collected by distributing questionnaires to customers who have used Tiki 0259 services in the last six months. Data analysis techniques used validity and reliability tests, multiple linear regression, and t-tests to test the influence of each independent variable on customer satisfaction as the dependent variable. The results showed that service quality and facilities had a positive and significant effect on customer satisfaction. The test showed that the facility variable had a more dominant influence compared to service quality, evidenced by the t-value of 20.075 which was greater than the t-table of 2.021 and a significance value of 0.000 <0.05. This means that improved facilities, such as comfortable waiting rooms, comprehensive digital services, and easy access to information, have a direct impact on customer satisfaction. These findings indicate the importance of continued investment in facility improvements and staff training to enhance service. Tiki management is advised to continuously evaluate available facilities and ensure professional, prompt, and friendly customer service. This way, Tiki 0259 can maintain customer loyalty and increase its competitiveness in the delivery services market. This research also provides empirical support for customer satisfaction-based service development strategies in the local logistics sector.